ACE and ACTN3 polymorphisms analysis on agility test in national players in team sports of Costa Rica. Pilot study - Carvajal-Espinoza, Rafael; Trejos-Montoya, José; Herrera-González, Emmanuel; Alemán-Ramírez, Carolina; Márquez-Barquero, Magally; Cervantes-Sanabria, Jorge; Loria-Calderón, Tyrone; Miranda-Benavides, Guillermo; Gutiérrez-Vargas, Randall (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2023)
Objective: To analyze the differences in the polymorphisms of the ACE and ACTN3 genes on agility test performance in elite players of collective sports from National teams of Costa Rica. Methods: a sample of 33 male team sports players (futsal, rugby, volleyball, and handball). All subjects were tested with the Illinois Agility Test. Two days of measurements were made; on the first day, cell samples were obtained and on the second day, the agility test was applied. The Chi-square test (x2) was used to determine the differences between the frequencies of the polymorphisms of the ACE and ACTN3 genes and the type of sport. Results: The highest distribution of polymorphisms of the ECA gene of players from national teams of collective sports was found in the ACE ID (X2 = 6.87, p = .334), and in ACTN3 the RX (X2 = 6.33, p =. 388). Furthermore, no significant relationship was found between the Illinois test performance and the polymorphisms of the ECA gene (F = 2,150, p = .134). Conclusions: The ACE and ACTN3 genes polymorphisms were not statistically related to the type of team sport. Agility is not associated with the type of polymorphism, which indicates that regardless of the gene, this physical quality can be trained and generate good results in the general population.